Perceptions Of Students, Teachers, and Parents Regarding the Implementation of the Numeraku Program in Strengthening the Values of Honesty and Numeracy at Wotgalih 03 Public Elementary School - Basukiyatno; Suriswo; Talkis Hasanudin (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to describe the perceptions of students, teachers, and parents regarding the implementation of the Numeraku Program in strengthening the values of honesty and numeracy at SD Negeri Wotgalih 03, Jatinegara District, Tegal Regency. This research adopts a qualitative literature review approach by drawing on books, journal articles, and relevant prior studies. The findings indicate that students generally perceive the Numeraku Program positively, as its contextual numeracy activities support the internalization of honesty in learning. Teachers play a crucial role as facilitators and role models in fostering honest behavior through reflective numeracy practices. Meanwhile, parents report observable positive behavioral changes at home, particularly in students’ responsibility and openness about their learning outcomes. The successful implementation of the Numeraku Program depends on strong collaboration among schools, teachers, and families in cultivating a culture of honesty and meaningful numeracy learning.